Communicative Fragments and Precedent Texts as Ways of Fixing the Linguistic Consciousness of Russian and Mongolian Native Speakers (on the Material of Animal Names) - Шкуропацкая , Марина Геннадьевна; Ундармаа, Даваа (Philology & Human, 2019)
The article presents the results of an experimental study of differences between the Mongolian and Russian language world views. The Russian and Mongolian native speakers acted as respondents. The material used was the words of the thematic group «pets» (e.g. cat) and domestic animals (e.g. cow). The respondents were offered lists of words and requested to write down an association phrase that contains this word. The analysis of the material resulted in the construction of association data fields, which reflect the communicative and epistemological experience of native speakers. The article presents an attempt to verify the hypothesis that texts of a certain sphere of communication (e.g., everyday communication) and thematic group are produced in both languages on the basis of a more or less stable potential of already existing lingual and speech structures (communicative fragments and precedent texts), that are characterized by national specificity.